Relationships within MOMS Orange County care coordinated home visitation perinatal program. Issue 2 (2nd December 2019) - Guo, Yuqing; Bender, Miriam; Rousseau, Julie; Kehoe, Priscilla; Lee, Jung‐Ah; Pimentel, Pamela; Bojorquez, Yvette; Silva, Michele; Olshansky, Ellen
Abstract: Purpose: The study aimed to examine how registered nurses (RNs) and paraprofessional home visitors (PHVs) work together as a team to care for underserved perinatal women in a coordinated home visitation program. Design and Methods: Qualitative methods were used to understand the perspectives of three RNs and twenty PHVs who worked at MOMS Orange County, a community‐based perinatal health program. Individual one‐on‐one interviews were administered with the RNs and focus groups with the PHVs. Qualitative content analysis was conducted to synthesize themes. Results: RNs perceived themselves as educators, mentors, and supervisors. PHVs thought of themselves as supporters, coaches, and advocates. Interdependence and proactive communication were favorable characteristics of the relationship in which RNs trained PHVs to provide health education. The positive interactions between RNs and PHVs appeared to enhance the client‐healthcare provider connection. Conclusions: Our study is one of the first to describe relationships and communication patterns among the healthcare team in a coordinated home visitation program in the United States. Future studies should examine how additional members of the team, including clients and healthcare providers, view their experiences with a home visitation program.